Expressive Utterances as Found in Zach Sang Show on YouTube - Mila Fitria; Ike Revita; Dhiant Asri (English Department, Faculty of Humanities, Andalas University, 2018)
This article analyses expressive utterances as found in Zach Sang Show on YouTube. This video is an interview of Zach Sang and the Gang to Selena Gomez as the guest of the show. The aim of this research is to analyse the types of expressive utterances and identify the functions of the expressive utterances found in the interview. Data were collected by using observational method and note-taking technique. Data were studied by using pragmatic identity method. Data were analyzed by using theory of types of expressive utterances proposed by Ronan (2015) and theory of function of expressive utterances proposed by Searle and Venderveken (1985). Data presented in narration and by using tables. Expressive utterances found in the video are 87 utterances. The writer finds 10 types of expressive utterance. They are agreement, volition, disagreement, compliment, pride, expressing sorrow, thanking, greetings, non-directed complaints in exclamations and apologizing. The most dominant type of expressive utterances is agreement. It shows the same perception between the speaker and the interlocutor. There are 14 functions of expressive utterance. They are to please, to desire, to agree, to disagree, to compliment, to boast, to lament, to thank, to greet, to complain, to surprise, to apologize, to congratulate and to praise. The most dominant function of the expressive utterances is to please. It shows the feeling of satisfaction, enjoyment and convenient to the proposition.